DAMPAK KENAIKAN HARGA KEDELAI PADA HOME INDUSTRY TAHU DI KABUPATEN SUKOHARJO - R, Erlyna Wida (Jurnal Dinamika Sosial Ekonomi, 2009)
Home industry soybean curd in Sukohatjo regency in this time have constraint that are increasing price and unstable soybean supply. Increasing price of soybean have chance producer possibility close down or desist to produce soybean curd because of production cost. The aims of this research are to 1) analysing impact of increasing price of soybean to main material cost proportion of home industry soybean curd and 2) analysing impact of increasing price of soybean to profit of home industry soybean curd. Research conducted in regency by taking district sampel is purposive that is having the amount of biggest soybean curd home industry. From Diperindagkop research area selected Nguter and Grogol district, while selected village are Plesan, Celep, Palangjoro and Madegondo. Responder counted is 30 producer by proporsional random sampling. Result of the research shows' that are 1) have deference of main material cost proportion of soybean to total expense which is signfican before and after soybean increase of price at home industry soybean curd, 2) have deference profit which is significan before and after soybean increase of price at home industry soybean curd.Key word : home industry, impact, increasing